Construction and cosmic-ray test of the new inner drift chamber for BESIII - 谢永骥 秦中华 马骁妍 张建 伍灵慧 谢万 董明义 董静 季筱璐 江晓山 欧阳群 朱科军 陈元柏 (Chinese physics C, 2016)
A new inner drift chamber has been built which can replace the aged part of the BESIII drift chamber when needed. The design of the new inner drift chamber can minimize the ineffective area in the very forward and backward region and hence reduce the background event rate. With this design, the new inner drift chamber is expected to have a longer lifetime and improved performance due to the lower occupancy. The endplates and the cylinder were machined with high precision. Wire stringing was performed after the mechanical structure was assembled, and good quality of wire stringing was ensured by measurement of the tension and leakage current of the wires. After completion of the physical construction of the new chamber, a cosmic-ray test was carried out to test its performance. The results of the cosmic-ray test show that the new inner chamber achieves a spatial resolution of127 μm and a d E/dx resolution of 6.4%, which satisfies the design specifications.